Women Demeanor at Warfare: Issues, Efficacy and Prospects - Kulkarni, Sneha (Advances in Social Sciences Research Journal, 2018)
Multiformity in the Armed Forces is a multiform subject, both in terms of vision and in terms of its more pragmatic, administrative meaning. It elaborates one of the utmost symbolic yet critical provocations for human resource management, especially regarding women recruits, that military leaders of Armed Forces have faced over the past few decades. Preeminent diversity in recruitment, reinforcement and services has challenged long established institutional norms, values, beliefs and attitudes in Armed Forces. Utilization of Women under human resource philosophies, policies, programs and practices have been adapted and revised. These revolutionary changes are accumulating evidence of the progress of Women in Military, which has been made in inspecting and responding diversity in the Armed Forces, along with the problems that remain unresolved; mainly focusing on complete synthesis of Women in Armed Forces, which seen as the most problematic; as many nations have yet to resolve gender-related issues. These forethoughts apply to numerous differences, which are essential to discuss, for enhancing efficacy of Women at War in general and Armed Forces in specific mannerism. The paramount target of this paper is young scholars having desire to join Indian Armed Forces; however authors with all level of proficiency may find useful intellection in the paper.